Diversity of Scolytinae, Platypodinae (Curculionidae) and Bostrichidae in Hevea brasiliensis (Willd. ex A.Juss.) in the state of Goias, Brazil - Tiago Neto, Lauro Joaquim; Pereira, Jaqueline Magalhaes; Rodrigues, Ohana Daroszewski; Lima, Nauara Lamaro; Froio, Leonardo de Lima [UNESP]; Hector Flechtmann, Carlos Alberto [UNESP] (Centro Pesquisas Florestais, Ufsm, 2022)
In Brazil, the rubber tree Hevea brasiliensis (Willd. ex A.Juss.) is heavily planted in the so-called escape areas in order to avoid leaf blight. While there are reports on damage inflicted by insects and mites in the literature, these are sparse. The objective of this study was to survey the community of Scolytinae, Platypodinae (Curculionidae) and Bostrichidae, in a rubber tree plantation in Goianesia, state of Goias, Brazil, with ethanol-baited flight intercept traps from March 2013 through March 2014. Scolytinae beetles (13 genera, 29 species) were the most abundant group, accounting for over 99% of trapped specimens, while six Bostrichidae, seven Cerambycidae and two Platypodinae species were also caught. Hypothenemus obscurus (Scolytinae) comprised ca. 89% of all trapped specimens. While no attack on live trees was observed during the survey, species with known ability to attack and successfully colonize standing trees were trapped in this study. Perhaps this is an indication that the plantation is well managed, not providing conditions where attacks on live trees may occur.
Keywords: Ambrosia beetles; Ethanol-baited trap; Seasonal variation